Terror in Utopia: Crisis (mis-) management during the COVID-19 pandemic in Sweden - Stilhoff Sörensen, Jens (Sociološki pregled, 2020)
This article provides an early account to document Swedens strategy to the COVID-19 pandemic and critically examines the countrys crisis response during the first six months of 2020. Sweden stood out internationally with a hands-off approach that gained much attention. Schools remained open, no lock-downs were underaken, no face masks reccommended, even in care homes, and testing-tracing-isolation was very limited. Although Swedens death rate per million was among the seven highest in the world during the period, there was no change in strategy. The article employs concepts to analyse and understand this peculiar approach and the secutity culture and political culture underpinning it. It uncovers deeper systemic defects and a breakdown in the state functions accompanyied by secrecy and cover-ups, as well as a totalitarian element in the political culture.